MENINGKATKAN KETERAMPILAN MEMAKAI JILBAB MELALUI MULTI METODE PADA ANAK TUNAGRAHITA SEDANG KELAS D.VI di SLB PERWARI PADANG - Yuni - Masriani (Universitas Negeri Padang, 2012)
This research of background overshadow from result of perception which is researcher in SLB Perwari Padang to two child people of Embisil class D.VI which still not yet skillful in wearing jilbab. Though to travel especially go to school to be obliged to wear jilbab. what in it there is two child people of embisil one teacher people. So that every day child have to be assisted by its old fellow. Pursuant to above mentioned the mentioned, researcher try to improve ability of child in wearing jilbab by using method multi. On that account this research aim to 1) Description process study to increase skill wear jilbab pass method multi, and 2) Proving method multi can uplift skill to wear child jilbab of embisil class D.VI in SLB Perwari Padang. This Research is lifted by using method research of class action (Classroom Action Research) with collaboration with coleage. Data collected to observation technique and of tes, laterthen analysed qualitative and is quantitative. Result of research indicate that 1) study process improve ability wear jilbab method multi done with two cycle. Cycle of I by Nine times cycle and meeting of II with six times meeting. Each meeting which early with activity of planning, final activity and execution 2) Result of study by using method multi the tes early value ability of Hn (6,25) and Tw still (0). Cycle of I assess ability of child mount namely: Hn (75) and Tw (52,5). While cycle of II increase to mount namely Hn obtain;get (93,75) and Tw (87,5) from eight activity step wear tested jilbab. Thereby, can be concluded that study with method multi can improve ability wear jilbab embisil of child at class D.VI SLB Perwari Padang. Suggested at school, researcher and teacher hereinafter to be able to use method multi in learning skill at embisil of child.